Climate change and our heritage of low carbon comfort. Issue 5 (27th May 2016) - Winter, Tim
Abstract: This paper examines the viability of maintaining a heritage of low carbon comfort as an alternative to the energy intensive comfort regime of mechanical air conditioning. In many parts of the world, the carbon footprint of buildings is increasing significantly due to the widespread adoption of air conditioning. Current trends around indoor comfort are unsustainable, and alternative, less energy intensive comfort regimes need to be maintained or cultivated. To date, studies on this topic in heritage and preservation studies have focused on the architectural designs of 'passive cooling'. This paper seeks to expand this conceptualisation of 'cool living heritage' to incorporate other forms of material culture and comfort practice.